The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1007/s11695-011-0416-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Transabdominal Ultrasonography (US) Prior to Laparoscopic Roux-en-Y Gastric Bypass (LRYGBP) and Laparoscopic Sleeve Gastrectomy (LSG) in the First 100 Operations. Was It Beneficial and Reliable During the Learning Curve?

Abstract: Preoperative US is unreliable in evaluating the size and consistency of the left lobe of the liver prior to LRYGBP and LSG and has limited prognostic value for surgical complications and complexity of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…[ 32 , 33 ] Standard abdominal ultrasound is characterized by low sensitivity and specificity in detecting a steatohepatitis. [ 34 – 36 ] Thus, in our study, we have observed concentrations of AST and ALT in the blood. In every step of the study the liver enzymes were between laboratory reference range values.…”
Section: Discussionmentioning
confidence: 49%
“…[ 32 , 33 ] Standard abdominal ultrasound is characterized by low sensitivity and specificity in detecting a steatohepatitis. [ 34 – 36 ] Thus, in our study, we have observed concentrations of AST and ALT in the blood. In every step of the study the liver enzymes were between laboratory reference range values.…”
Section: Discussionmentioning
confidence: 49%
“…In the past, Fris [3] and Jaser et al [7] in their respective studies have described techniques for left liver lobe measurement on ultrasound performed in obese patients. These studies reveal two different techniques; one study measured the factor of the volume of left lobe of liver [3].…”
Section: Discussionmentioning
confidence: 99%
“…These studies reveal two different techniques; one study measured the factor of the volume of left lobe of liver [3]. The other study considered the left lobe of liver to be enlarged if there was rounding of the liver border along with the largest sagittal diameter of the left lobe of the liver in the plane of abdominal aorta measuring over 12-cm OR extension of the left border of the liver by over 8 cm from midline at the plane of pancreas and the AP measure of the left lobe of the liver in the plane of abdominal aorta being over 8 cm [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that even in 60% of patients, obesity is connected with steatosis, including 55% of the pediatric population [27][28][29][30]. Despite routine abdominal ultrasonography, which according to different authors has low sensitivity and specificity in recognition of liver steatosis, measures of aminotransferases activity have been performed in all patients [31].…”
Section: Discussionmentioning
confidence: 99%